Pre-clinical evaluation of an adult extracorporeal carbon dioxide removal system for pediatric application - Mussin, Y.; Jeffries, R.; Bulanin, D.; Zhumadilov, Zh.; Olzhayev, F.; Federspiel, W. (Nazarbayev University, 2014)
Adult extracorporeal carbon dioxide removal (ECCO2R) systems and pediatric ECMO share the common objectives of having a low blood flow rate and low priming volume while safely maintaining sufficient respiratory support. The Hemolung is a highly simplified adult ECCO2R system intended for partial respiratory support in adult patients with acute hypercapnic respiratory failure.
Keywords: adult extracorporeal; carbon dioxide; blood; hypercapnic respiratory; anesthesia; pulmonary artery